Aquatic strength training improves postural stability and walking function in stroke patients - Gu, Xudong; Zeng, Ming; Cui, Yao; Fu, Jianming; Li, Yan; Yao, Yunhai; Shen, Fang; Sun, Ya; Wang, Zhongli; Deng, Dingyi (Physiotherapy theory and practice, 2023)
This study aims to explore the effects of aquatic strength training on the postural balance and walking function of stroke patients. A total of 56 chronic stroke patients more than 6 months post-stroke with walking and balance impairments were included in this study. After baseline evaluations, patients were randomly assigned to either the experiment group (n = 29) or control group (n = 27). Patients in the control group underwent conventional hydrotherapy, whereas patients in the experiment group received conventional hydrotherapy combined with aquatic lower extremity strength training. After six weeks of rehabilitation, all patients were evaluated by a blinded assessor, and the functional assessments including: Berg Balance Scale (BBS); Timed Up and Go Test (TUG and mTUG); 2 Minute Walk Test (2MWMT); and Gait analysis. There were no significant differences (P > .05) between the two groups in all evaluation indexes before rehabilitation. Six weeks after treatments, the results from both groups showed significant improvements compared with those in the baseline evaluations (P < .05). Notably, compared with the control group, BBS, TUG and mTUG, 2MWMT, and Gait analysis including stride length in the non-hemiplegic side, stride length, as well as walking speed and stride frequency in the hemiplegic side in experiment group were markedly improved (P < .05). Aquatic strength training can improve postural balance and lower extremity motor functions in chronic stroke patients.